2017
DOI: 10.3390/ijms18061228
|View full text |Cite
|
Sign up to set email alerts
|

BrWRKY65, a WRKY Transcription Factor, Is Involved in Regulating Three Leaf Senescence-Associated Genes in Chinese Flowering Cabbage

Abstract: Plant-specific WRKY transcription factors (TFs) have been implicated to function as regulators of leaf senescence, but their association with postharvest leaf senescence of economically important leafy vegetables, is poorly understood. In this work, the characterization of a Group IIe WRKY TF, BrWRKY65, from Chinese flowering cabbage (Brassica rapa var. parachinensis) is reported. The expression of BrWRKY65 was up-regulated following leaf chlorophyll degradation and yellowing during postharvest senescence. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…35 Relative electrolytic leakage was determined as previously described. 3 RNA Extraction, cDNA Synthesis, Gene Cloning and Sequence Analysis. Total RNA of sampled tissues was isolated by use of an RNeasy plant mini kit (Qiagen) according to the manufacturer's instructions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Relative electrolytic leakage was determined as previously described. 3 RNA Extraction, cDNA Synthesis, Gene Cloning and Sequence Analysis. Total RNA of sampled tissues was isolated by use of an RNeasy plant mini kit (Qiagen) according to the manufacturer's instructions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In our previous study, we also found that BrWRKY65 from Chinese flowering cabbage may be acting as a positive regulator of leaf senescence by activating three senescence-associated genes (SAGs). 3 Moreover, WRKY TFs are demonstrated to be involved in various physiological processes controlled by GA. 30 For instance, three WRKY TFs of rice, including OsWRKY24, -53, and -70, negatively regulate GA signaling in aleurone cells. 31 WRKY12 and WRKY13 mediate the GA 3 -controlled flowering time in Arabidopsis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It often suffers from high-temperature stress in summer 6 , which not only influences plant growth and performance but results in yield reductions and even death 7 . Flowering Chinese cabbage genotypes can have obvious premature leaf senility, fine flowering stalks, significantly reduced photosynthetic capacity, and high electrolytic leakage and malondialdehyde content under high-temperature condition 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…WRKY TFs can be divided into three groups [I, II (IIa-e), and III] on the basis of their structure and evolutionary history (Eulgem et al, 2000; Rushton et al, 2010). WRKY TFs can interact with W-box cis-elements [TTGAC(C/T)] in the promoter regions of downstream genes to regulate the expression of those genes, thus leading to improved plant adaptation to environmental changes (Fan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In rice, OsWRKY23 has been shown to be involved in dark-induced leaf senescence in transgenic Arabidopsis plants (Jing et al, 2009). WRKY TFs are also involved in vegetative and fruit senescence, including BrWRKY65 in Chinese flowering cabbage (Fan et al, 2017) and LcWRKY1 in litchi (Jiang et al, 2017). Two cotton WRKY TFs, GhWRKY27 (Gu et al, 2019) and GhWRKY42 (Gu et al, 2018b), were recently identified to promote leaf senescence in transgenic Arabidopsis plants, suggesting that WRKY TFs have important roles during leaf senescence in cotton.…”
Section: Introductionmentioning
confidence: 99%